A BRIEF LOOK INTO FOOD COSTING (Case Study Towards Purchasing and Inventory Management) - Hilda Tjahjani Iskandar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This article describes how foodservice managers can effectively manage cost con-trol in the workplace. Ultimately, this study helps us to better understand how cost control in the food industry can help control expenses and undue costs due to un-expected events. Foodservice managers must understand and manage costs related to their business operations. The foodservice manager, whether in a restaurant, ho-tel, or institution, has to undertake a myriad of responsibilities, be it accounting, marketing, human relations, general affairs, building and facilities management in-cluding maintenance and sanitation, legal issues, waste management, production, and service methods, amongst others. Keywords: Foodservice Manager, Cost Control, Control Expenses, Inventory Management, Purchasing